Masochisme mortifère et masochisme gardien de la vie Broché - Rosenberg, Benno (Presses universitaires de France, 2003)
Introduction: Fundamental issues in sexual deviance / D. Richard Laws and William O'Donohue * Exhibitionism: Psychopathology and theory / William D. Murphy * Exhibitionism: Assessment and treatment / Barry M. Maletzky * Fetishism: Psychopathology and theory / Fiona L. Mason * Fetishism: Assessment and treatment / John Junginger * Frotteurism: The theory of courtship disorder / Kurt Freund, Michael C. Seto and Michael Kuban * Frotteurism: Assessment and treatment / Richard B. Krueger and Meg S. Kaplan * Pedophilia: Psychopathology and theory / W. L. Marshall * Pedophilia: Assessment and treatment / Howard E. Barbaree and Michael C. Seto * Sexual sadism: Psychopathology and theory / Stephen J. Hucker * Sexual sadism: Assessment and treatment / Clive R. Hollin * Sexual masochism: Deviance without pathology / Roy F. Baumeister and Jennifer L. Butler * Sexual masochism: Assessment and treatment / David Thornton and Ruth Mann * Transvestic fetishism: Psychopathology and theory / Kenneth J. Zucker and Ray Blanchard * Transvestic fetishism: Assessment and treatment / Gwen Adshead * Voyeurism: Psychopathology and theory / Meg S. Kaplan and Richard B. Krueger * Voyeurism: Assessment and treatment / R. Karl Hanson and Andrew J. R. Harris * Rape: Psychopathology and theory / Stephen M. Hudson and Tony Ward * Rape: Assessment and treatment / Tony Ward, Julie McCormack, Stephen M. Hudson and Devon Polaschek * Paraphilia not otherwise specified: Psychopathology and theory / Joel S. Milner and Cynthia A. Dopke * Paraphilia not otherwise specified: Assessment and treatment / Paul A. Schewe * Medical models of sexual deviance / Don Grubin and Debbie Mason * Medical interventions in sexual deviance / John Bradford * Sexual deviance in females / John A. Hunter and Ruth Mathews Future directions / Stephen M. Hudson and Tony Ward